(untitled) (Heritage, 2021)
On the sample of 84 Serbian companies which operate on Kosovo territory (Serbian enclaves) in post-conflict situation we want to find out which factors are crucial for their survival and success. Also we want to find out is EU regulatory document for small enterprises helpful for them in this situation. We did not find EU document helpful in this situation. The results have confirmed that the enterprises are aware that expanding the market range is the only real and sustainable method of developing their activities. The key limiting factor in expanding the market range is the unfair competition. Furthermore, we are particularly pleased with the fact that enterprises from the northern part of Kosovo and Metohia are aware of the importance of innovative activities, and they realized that in contemporary business world it is possible to survive and grow in the market only by developing and introducing innovations. There are no universal solutions in a post-conflict situations. Search for ideal solution for developing the entrepreneur activities and it depends on the combination of social/political, institutional, cultural and economic aspects.